Climate anxiety as a call to global justice - Batul Hanife; Paolo Cianconi; Francesco Grillo; Alexis Paulinich; Luigi Janiri (Frontiers in Psychology)
Climate anxiety (or eco-anxiety) is a growing psychological phenomenon linked to the increasing awareness of the environmental crisis caused by climate change. However, it is better understood within the context of the anthropogenic mechanisms that have contributed to pollution and climate change and that are failing to control their consequences, creating a sense of mistrust and uncertainty toward the national and international institutions. Moreover, the impacts of climate change are unequally felt by the rich and the poor also across generations, and policies designed to manage climate change have starkly unequal consequences and the processes by which are decided tend to exclude the poor and the powerless. Nevertheless, even if the groups most at risk for climate change consequences are minorities and marginalized communities, it does not appear that they are the main subjects of criticism and protest, and respondents of color appear to be more likely than white respondents to report feeling traumatized, but less likely to report feeling most of the negative emotions and more likely to feel optimistic and hopeful. Those findings in literature opens the discussion to many questions. Could this apparent discrepancy in climate anxiety reports indicate a difference in historical and cultural perceptions of climate change? Can we consider climate anxiety as a cultural syndrome? Can recognizing these differences in the expression of climate anxiety raise awareness of the unequal impacts of climate change itself and the priority of tackling climate injustice?